The aims of this study is to idenffy the affect of using mulity educational daids in teaching some basic akills in Volley ball - Abed, Nahida (Journal of Physical Education, 2008)
The researcher used expermental style of one group design by wed the students of four class of tearchers preparation in stouate in babylon-(N:12) same teavhing aids used in the expermental. Some pne-teats used( skills tests) after making exploratory expermental. The main program gave to the sample with the educotional aids . for 8 weeks by two teaching unites per aweek, the same tests were donein the post tests(T-Test,main, standand devation) a signiff icint . The conclusions of the study dicoted effect of educational aids on teaching volley ball skills.